(untitled) (Research, Society and Development, 2020)
Pain is a subjective experience, experienced individually, and directly affects the individual’s quality of life. The number of visits to emergency units is quite significant, for this reason, pain scales have been implanted - since this is considered the fifth vital sign - in order to measure it and, thus, offer humanized assistance. The aim of the study was to analyze scientific productions about the use of the pain scale in hospital emergency units in the national context. This is an integrative review research. The search for scientific articles was carried out in the SciELO database, using the terms "pain scale" and "urgency and emergency" in all fields, and "nursing" in the area of knowledge. The results obtained revealed that the demand for users with acute pain in the Urgency and Emergency units increased, and that the evaluation as well as the use of instruments for pain assessment in these units are carried out, however there is a need to expand knowledge that envisages the update professional. It is concluded that a quality assessment of the patient in Urgency and Emergency units is essential, with a view to better clinical management, and it is up to the nurse to train and lead their teams so that quality care is provided to users.